The Differences Patient Satisfaction Indices Using Android application and Questionnaire Method in The Puskesmas - I Gusti Lanang Putu Udiyana; I Gede Riana (Journal of Multidisciplinary Academic, 2021)
Satisfaction assessment in a health centre is an important part of evaluating service quality. Nowadays, health centres are common to input and processing the satisfaction index data in conventional process (manual) from questionnaires. So that, the service reporting cannot be done quickly and quality evaluation. Thus, in this study aims to examine the differences over patient satisfaction using e-questionnaire on android and conventional questionnaire method at public health centre (Puskesmas). This research we descriptive a several questionnaires and compared with 162 samples using purposive sampling technique. Here, Mann Whitney method was performed to analyse the data observation. The test results show a sig value of 0.985 (P value> 0.05), which means that there are no significant differences between the index of patient satisfaction using the Android and the questionnaire method. These results indicate an android assessment that can be applied to the satisfaction index assessment for the effectiveness and efficiency of the satisfaction index assessor.